Case report: Successful outcome of treatment using rituximab in an adult patient with refractory minimal change disease and β-thalassemia complicating autoimmune hemolytic anemia - Zhuang, Jing; Zhao, Zhigang; Zhang, Changrong; Song, Xue; Lu, Chen; Tian, Xuefei; Jiang, Hong (Frontiers in Medicine, 2022)
Minimal change disease (MCD) is one of the common causes of idiopathic nephrotic syndrome (INS), accounting for 10%-20% of INS in adults. Glucocorticoids are the most commonly used and effective drugs in the treatment of MCD, but there is still a proportion of adult patients with MCD who are characterized by glucocorticoid resistance, glucocorticoid dependence, and frequent relapse, which are defined as refractory nephrotic syndrome. Glucocorticoid combination with immunosuppressants is frequently used in patients with refractory nephrotic syndrome, and patients concerned about adverse effects caused by long-term high-dose glucocorticoid therapy. Recent studies have suggested that Rituximab (RTX), a chimeric monoclonal antibody targeted against the pan-B-cell marker CD20, combined with a small or medium dose of glucocorticoid has a beneficial effect with less adverse effects on adult patients with refractory MCD. β-thalassemia is an inherited hemoglobulin disorder caused by the mutation of genes that encode β-globin and results in ineffective erythropoiesis. We here report a case of an adult patient with refractory MCD complicated with β-thalassemia minor accompanied by autoimmune hemolytic anemia. MCD relapsed several times despite treatment using glucocorticoid combined with or without different immunosuppressive agent regimens. The β-thalassemia minor was caused by heterozygosity for a 4-base deletion mutation (codons 41/42 (-TTCT) BETA0) of the β-globin gene. After the administration of RTX, MCD achieved clinical complete remission, and the anemia due to mild β-thalassemia recovered to normal as well. The disease situation remained stable during 36 months of follow-up. These findings suggest that RTX may contribute to the improvement of refractory MCD and anemia in β-thalassemia minor accompanied by autoimmune hemolytic anemia.